Analysis of students performance in relation to the results of state unified exam: the case of Russian university - Svirina, Anna; Lopatin, Aleksey; Titko, Jelena (Business, Management and Economics Engineering, 2021)
Purpose – Considering the limited number of studies covering the topic, the goal is to check the existence of the correlation between the results of Russia’s Unified State Exam and performance at the university.Research methodology – the article uses quantitate analysis (regression) of the student performance on a sample of 4664 students. To provide statistical evaluation, the authors use SPSS Statistics software.Findings – the research suggests, that results of unified state exam and individual students scores, awarded by the university under restrictions, are non-efficient in terms of predicting student performance. On the opposite, students’ performance during their first semester is a good predictor for the whole period of academic studies. As existing results of testing such hypotheses are inconsistent, the research provides value to the field of educational research.Research limitations – data for research refer to only Kazan National Research Technical University named after A. N. Tupolev (KNRTU-KAI).Practical implications – the research clearly indicate, that the universities cannot rely solely on the unified state exam during admission; they are to use different assessment tools to ensure future academic performance and lower dropouts rate.Originality/Value – There is a gap in the investigation the link between secondary education and higher education performance.